Association of SNPs in the FK-506 binding protein (FKBP5) gene among Han Chinese women with polycystic ovary syndrome - Xinyue Ma; Zhao Wang; Changming Zhang; Yuehong Bian; Xin Zhang; Xin Liu; Yongzhi Cao; Yueran Zhao (BMC, 2022)
Abstract Background Polycystic ovary syndrome (PCOS) is a common endocrine disorder in premenopausal women, whose etiology remains uncertain, although it is known to be highly heterogeneous and genetically complex. PCOS often presents with hyperandrogenism symptoms. The present study aimed to determine whether polymorphisms in the FK-506 binding protein 5 (FKBP5) gene (androgen target gene) are associated with an association for PCOS and hyperandrogenism. Methods This is a case-control study, and association analyses were conducted. A total of 13 single-nucleotide polymorphisms (SNPs) in the FKBP5 gene were evaluated in 775 PCOS patients who were diagnosed based on the Rotterdam Standard and 783 healthy Chinese Han women. Associations between FKBP5 SNPs and hormone levels were investigated. These 13 SNPs were genotyped using the Sequenom MassARRAY system, and an association analysis between the phenotype and alleles and genotypes were conducted. Results The genotype frequencies for the rs1360780 and rs3800373 SNPs differed significantly between the PCOS cases and healthy controls (p = 0.025, OR is 1.63 (1.05-2.53) and p = 0.029, OR is 1.59 (1.03-2.45) respectively under co-dominant model). Moreover, the genotype frequencies and genetic model analysis for the SNPs rs1360780, rs9470080, rs9296158, rs1043805 and rs7757037 differed significantly between the hyperandrogenism and non-hyperandrogenism groups of PCOS patients. The TT genotype of rs1360780, the TT genotype of rs9470080, the TT genotype of rs1043805 or the GG genotype of rs7705037 (ORs are 2.13 (1.03-4.39), 1.81 (1.03-3.17), 2.94 (1.32-6.53) and 1.72 (1.04-2.84) respectively) were correlated with androgen level of PCOS patients. Conclusion Our study showed that FKBP5 gene polymorphisms are associated with PCOS generally (rs1360780 and rs3800373) and with the hyperandrogenism subtype specifically (rs1360780, rs9470080, rs9296158, rs1043805 and rs7757037).